Brain morphometry of HIV-infected children on early antiretroviral therapy (ART) from age 5 to 9 years - Nwosu, Emmanual Chukwubuikem (Department of Human Biology, 2020)
As of 2017, 1.8 – 2.1 million children vertically infected with HIV were living in sub-Saharan Africa, of whom an estimated 320, 000 were in South Africa. Since implementation of the prevention of mother to child transmission (PMTCT) strategy, the infection rate has reduced substantially. More recently, the World Health Organisation's (WHO) recommendation of early antiretroviral therapy (ART) initiation for children with perinatal HIV infection has considerably decreased the immediate effects of perinatal HIV infection, including mortality and morbidity. Despite this, not much is known about the long-term outcome of continued ART on early-treated, perinatally HIV-infected children. Early HIV invasion of the developing brain is associated with neurodevelopmental delays and neurocognitive deficits including encephalopathy, slower processing speed, language impairment, lack of concentration and attentiveness, and psychomotor slowing. Alterations in the neurodevelopmental trajectories of brain morphology, including cortical thickness and folding (gyrification) and sub-cortical volumes may be related to the observed neurocognitive deficits during a critical period of brain development spanning from mid-childhood into early adolescence (age 5 -13 years). The effects may be studied using structural magnetic resonance imaging (MRI) and automated segmentation software. FreeSurfer (https://surfer.nmr.mgh.harvard.edu/) is a valuable tool for investigating brain morphology but was not originally designed for segmenting pediatric brains. In this study we therefore first validate the latest FreeSurfer version 6.0.0 against manual segmentation for the study of pediatric HIV. We then assessed the long-term effects of perinatal HIV infection, early ART initiation as well as clinically designed ART interruption, HIV-related encephalopathy, disease severity at ART initiation and immune health measures on the developmental trajectories of cortical thickness and folding (gyrification) over the period from 5-9 years. Study participants were 141 children (75 HIV+, 66 uninfected controls; 72 male) from the Cape Town arm of the children with HIV early antiretroviral therapy (CHER) clinical trial. HIV+ children were randomized at age 6 -12 weeks to receive either immediate limited ART for 40 or 96 weeks, to be restarted when clinical and/or immunological criteria were met, or to start ART only when they developed HIV symptoms or CD4 percentage dropped below 20% (25% in the first year) as per guidelines at the time. Uninfected controls comprised children born to HIV+ mothers (HIV-exposed uninfected (HEU)) or uninfected mothers (HIV-unexposed (HU)) and were recruited from an interlinking vaccine trial. MRI scans were performed at time points around their 5th, 7th and 9th birthdays, in accordance with protocols approved by the human research ethics committees of the Universities of Stellenbosch and Cape Town and voluntary informed consent was received from either participants or their guardians. Both automated and manual methods were used to segment brain regions from high-resolution structural MRI scans. In addition, FreeSurfer was used to examine cross-sectional differences in cortical thickness and gyrification over the cortical surface at age 5. Linear mixed-effects models were used in conjunction with FreeSurfer's longitudinal processing stream to calculate and compare the annual rate of change in cortical thickness and gyrification between ages 5 and 9 in HIV+ children and controls. Results showed that automated FreeSurfer segmentation tended to overestimate volumes of all structures relative to manual segmentation, except the left caudate nucleus. Consistency and agreement between methods were highest for the putamen (Consistency: right ICC=0.89, left ICC=0.90; agreement: right ICC=0.84, left ICC=0.83) and lowest for the corpus callosum (consistency ICC=0.64, agreement ICC=0.26). There were no subcortical volume differences between HIV+ children and controls, except the globus pallidus which was smaller in HIV+ children using both manual and automated segmentation. Subsequent cross-sectional FreeSurfer analyses showed widespread regional increases in cortical thickness and decreases in gyrification at age 5 years, related to the effects of perinatal HIV-infection and early ART initiation. Clinically designed interruption led to thicker cortex in the left rostral middle frontal and right insula regions and, lower left precuneus and right superior frontal, as well as higher lateral occipital gyrification compared to HIV- controls. There were significant regional differences due to HIV severity based on CDC classification and viral burden at enrolment both in cortical thickness and gyrification compared to controls. Cortical thickness was not associated with immune health parameters, while gyrification was negatively associated with immune health measures. However, the linear rate of change of cortical thickness and gyrification from age 5 to 9 in the HIV+ children was not different from that of uninfected controls, nor was it different between controls and children on interrupted or continuous ART. Children with HIV-related encephalopathy showed a decrease in gyrification with age during this period, in contrast to controls who showed stable gyrification except in frontal regions where gyrification increased with age. Children with perinatal HIV infection display alterations in cortical development due to ART interruption and disease severity at age 5 years, despite starting ART early in life. Our results suggest that cortical gyrification is more sensitive than cortical thickness to effects of perinatal HIV infection. ART interruption and disease severity at ART initiation affect cortical morphometry development at age 5 years in a perinatally infected, early-treated pediatric cohort. However, on continued ART the cortical developmental trajectory is no different from that of uninfected controls. Any structural defects resulting from ART interruption appear to normalise by age 9, except in children with HIV-related encephalopathy, who show an altered trajectory of gyrification development.